Determining the moment-rotation curve for top and seat angle and stiffened welded-seat connections using Chisala’s model - Nader Fanaie; Mehdi Fazli; Mohammad Amin Moghaddasi (Numerical Methods in Civil Engineering)
This research aims to investigate the analytical procedure of constructing the moment-rotation curve for top and seat angle, and stiffened welded-seat connections using Chisala’s model. As these connections practically exhibit a semi-rigid flexural performance, the moment-rotation curve appears to provide useful information and helpful vision on their performance for design engineers. Since the process of determining the precise moment-rotation curve for a steel connection is costly due to the need for laboratory experiments or heavy finite element computations, using a precise and straightforward analytical model appears to be more feasible. Chisala’s model, having fewer and independent parameters, is precise and easy to construct, which is fit for the purpose. In this regard, the procedure of constructing the analytical model for both types of connections using Chisala’s model is explained, and the key parameters of Chisala’s model are determined. As a means of verification, finite element models of both types of connections were constructed as well, using Abaqus software. To ensure that the results are not accidental, a total of 34 TSA (Top and Seat Angle), and 33 SWS (Stiffened Welded-Seat) connection specimens with different geometric dimensions were tested, and the effects of geometric dimensions on the flexural performance of each type as side results were described. Based on the obtained data, analytical and numerical moment-rotation curves, for both types of connections, were illustrated. The results suggest that Chisala’s model can precisely predict the moment-rotation curve for the mentioned types of connections, provided that a proper equivalent analytical model is created